Studi Komparasi Hukum atas Perlindungan Hukum Hak Cipta pada Media Elektronik dalam Common Law dan Civil Law - Marsella Marsella; Jelly Leviza (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This article aims to compare the legal protection of copyright in electronic media in common law and civil law. This research adopts normative legal research methods. This method is used to understand, explain, and evaluate normative aspects of the legal system. The research results show that the Common Law system relies on precedents and previous court decisions as the main source of law. Copyright laws may be more general and may evolve through court interpretation. Copyright is automatically granted when a creative work is created without formal registration requirements. Meanwhile, the Civil Law system has more detailed and codified coverage of the law. Copyright law is often regulated in specific and detailed copyright statutes. In some Civil Law systems, copyright registration is an important requirement to obtain legal protection. Copyright may not be granted automatically and requires registration steps. Similarities in Copyright Protection The Common Law and Civil Law legal systems lie in the legal system generally recognizing copyright as the exclusive right of the owner of a work to control the use and distribution of his work. In the context of international protection, both Common Law and Civil Law generally follow international agreements such as the Berne Convention to protect copyright across borders.